The use of Passive Acoustic Monitoring as an auxiliary tool for monitoring Marine Protected Areas - Ana Clara B. Mariani; Silvia N. Godoy; Marcos César de O. Santos (Ocean and Coastal Research)
Marine Protected Areas (MPAs) in Brazil, like the “Refúgio de Vida Silvestre do Arquipélago de Alcatrazes”(REVIS de Alcatrazes), contain great species diversity. For conservation purposes, investing in local monitoring and surveillance is necessary. In this sense, Passive Acoustic Monitoring (PAM) has been used to collect acoustic data from marine environments. Therefore, this study assessed the frequency of vessels in the mentioned MPA in 2019 using PAM. Audio records collected by a hydrophone anchored at Saco do Funil (24°05’S; 45°41’O), located around 500 m from the main island of the archipelago, were used. Each audio file underwent a visual inspection of the spectrograms to detect the acoustic signals. The noise related to vessels transit was identified in 10% of the analyzed files, of which approximately 46% of the occurrences did not correspond to visits by the MPA management office. The area was most frequented from 6 am to 2 pm. The occurrence of non-official and unauthorized vessels was mostly concentrated from 3 am to 6 am and at 0 am. The study also underscored the biological significance of the MPA, revealing this area potential to be regularly visited by baleen whales in July and toothed whales throughout the analyzed months. So far, this is the only known surveillance investigation that used the PAM in MPAs along the Brazilian coast. Improvement and expansion of this technique use may lead using acoustics as an important auxiliary tool in monitoring MPAs on the Brazilian coast.